Med rec double check: Inpatient psychiatry medication errors identified on admission using Medicaid Web portals and electronic pharmaceutical claims data - Su Su E. Oo, PharmD candidate; Ian R. McGrane, PharmD (American Association of Psychiatric Pharmacists, 2024)
Introduction The role of pharmacists during medication reconciliation (MR) is well established, with a number of reports describing this in the context of psychiatric hospitalizations. However, medication errors (MEs) are common during transitions of care, with no exception during psychiatric hospitalizations. Our institution uses pharmacy-performed MR processes using patient interviews and reviewing objective sources, such as electronic pharmaceutical claims data (EPCD), which includes Medicaid Web portals. The inpatient psychiatric pharmacist reviews EPCD sources against previously pharmacy-completed MRs for new admissions, where if discrepancies are found, the patient is reinterviewed to identify and correct MEs. Methods We performed a prospective quality improvement project during 28 days to evaluate the quantity and classification of MEs upon admission to a 22-bed inpatient psychiatry unit. Results Of 52 included patients, where a cumulative 426 medications were reviewed, a total of 29 MEs in 16 patients were identified. Eight patients had discrepancies on their home medication lists when compared to EPCD, where 7 of these had at least 1 ME due to inaccurate MR. Discussion Of all the MEs identified, the greatest quantity was found secondary to the EPCD "double-check" method. The most common MEs in all patients were the omission of home medications (34%), wrong frequency (28%), and ordering medication the patient is not taking (10%). All patients admitted on long-acting injection antipsychotics had errors in last dose received. No MEs resulted in patient harm, and they were identified and corrected by the psychiatric pharmacist 97% of the time.